Neuromodulation of Glial Function During Neurodegeneration - Stevenson, Rebecca; Samokhina, Evgeniia; Rossetti, Ilaria; Morley, John W.; Buskila, Yossi (Frontiers in Cellular Neuroscience, 2020)
Glia, a non-excitable cell type once considered merely as the connective tissue between neurons, is nowadays acknowledged for its essential contribution to multiple physiological processes including learning, memory formation, excitability, synaptic plasticity, ion homeostasis, and energy metabolism. Moreover, as glia are key players in the brain immune system and provide structural and nutritional support for neurons, they are intimately involved in multiple neurological disorders. Recent advances have demonstrated that glial cells, specifically microglia and astroglia, are involved in several neurodegenerative diseases including Amyotrophic lateral sclerosis (ALS), Epilepsy, Parkinson’s disease (PD), Alzheimer’s disease (AD), and frontotemporal dementia (FTD). While there is compelling evidence for glial modulation of synaptic formation and regulation that affect neuronal signal processing and activity, in this manuscript we will review recent findings on neuronal activity that affect glial function, specifically during neurodegenerative disorders. We will discuss the nature of each glial malfunction, its specificity to each disorder, overall contribution to the disease progression and assess its potential as a future therapeutic target.